UNDERSTANDING EFFECTIVENESS OF NATIONALIZED BANK SCHEMES ON THE SUCCESS OF WOMEN ENTREPRENEURSHIP - Gawande, Sonal Dashrath; Kotkar, Shamkant Narhar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study evaluates the effectiveness of nationalized bank schemes in promoting the success of women entrepreneurship in India. Over the years, nationalized banks have launched various financial products and support programs aimed at empowering women entrepreneurs, such as the Stand Up India Scheme, Pradhan Mantri Mudra Yojana, and Mahila Udyam Nidhi. The research employs a quantitative approach, utilizing a structured survey of 250 women entrepreneurs who have benefited from these schemes. The study explores the impact of these financial products on business growth, access to financial resources, training, and sustainability. The results indicate that nationalized bank schemes have positively influenced women entrepreneurs, particularly in terms of improving access to finance and fostering business expansion. However, the study also identifies persistent challenges, including societal barriers, limited access to business networks, and the difficulty in balancing family responsibilities with business operations. Despite the positive outcomes, these ongoing challenges suggest the need for a more holistic approach, combining financial support with mentorship, networking, and policies that address socio-cultural barriers. The study concludes with recommendations for enhancing the effectiveness of these schemes, calling for a more inclusive and comprehensive support system for women entrepreneurs in India.